UPAYA PENCEGAHAN PENULARAN PENYAKIT TB PARU DI WILAYAH KERJA UPT PUSKESMAS LIMA KAUM I KABUPATEN TANAH DATAR - Satria, Eka Budi; Maisyarah, Maisyarah; Athosra, Athosra; Meladina, Meladina (Universitas Fort De Kock, 2024)
Tuberculosis is an infectious disease caused by Mycrobaterium Tubercolusis, one of the health problems in Indonesia, TB control is one of the commitments of the SDGs program. In Tanah Datar district in 2019 there was another increase to 460 cases while the working area of Health Center Lima Kaum I recorded 12 cases of tuberculosis in 2022. This type of research is descriptive analytical with a cross-sectional study approach. The population in this study was the entire population in the working area of Health Center Lima Kaum I, which was 31,307 people. Sampling used a proportional sampling technique with a sample size of 100 people who met the inclusion criteria. The independent variables are knowledge, motivation, family support and the dependent variable is efforts to prevent transmission of tuberculosis. The results of the study showed that there was a relationship between knowledge p value (0.001), family support p value (0.000) and motivation p value (0.004) with efforts to prevent transmission of tuberculosis. The conclusion is that family support plays the most important role in the implementation of efforts to prevent transmission of tuberculosis. It is hoped that officers will provide education to families who have not carried out TB prevention